Alkaline pH Promotes NADPH Oxidase-Independent Neutrophil Extracellular Trap Formation: A Matter of Mitochondrial Reactive Oxygen Species Generation and Citrullination and Cleavage of Histone - Naffah de Souza, Cristiane; Breda, Leandro C. D.; Khan, Meraj A.; Almeida, Sandro Rogério de; Câmara, Niels Olsen Saraiva; Sweezey, Neil; Palaniyar, Nades (Frontiers in Immunology, 2018)
pH is highly variable in different tissues, and affects many enzymatic reactions in neutrophils. In response to calcium ionophores such as A23187 and ionomycin, neutrophils undergo nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX)-independent neutrophil extracellular trap (NET) formation (NETosis). However, how pH influences the calcium-dependent Nox-independent NET formation is not well understood. We hypothesized that increasing pH promotes Nox-independent NET formation by promoting calcium influx, mitochondrial reactive oxygen species (mROS) generation, histone citrullination and histone cleavage. Here we show that stimulating human neutrophils isolated from peripheral blood with calcium ionophore A23187 or ionomycin in the media with increasing extracellular pH (6.6, 6.8, 7.0, 7.2, 7.4, 7.8) drastically increases intracellular pH within in 10-20 min. These intracellular pH values are much higher compared to unstimulated cells placed in the media with corresponding pH values. Raising pH slightly and drastically increase intracellular calcium concentration in resting and stimulated neutrophils, respectively. Like calcium, mitochondrial reactive oxygen species (mROS) generation also increases with increasing pH. A mROS scavenger, MitoTempo, significantly suppresses calcium ionophore-mediated NET formation with a greater effect at higher pH indicates that mROS production is at least partly responsible for pH-dependent suppression of Nox-independent NETosis. In addition, raising pH increases PAD4 activity as determined by the citrullination of histone (CitH3) and histone cleavage determined by Western blots. The pH-dependent histone cleavage is reproducibly very high during ionomycin-induced NETosis compared to A23187-induced NETosis. Little or no histone cleavage was noted in unstimulated cells, at any pH. Both CitH3 and cleavage of histones facilitate DNA decondensation. Therefore, alkaline pH promotes the intracellular calcium influx, mROS generation, PAD4-mediated CitH3 formation, histone 4 cleavage and eventual NET formation. Calcium-mediated NET formation and CitH3 formation is often related to sterile inflammation. Hence, understanding of these important mechanistic steps helps to explain how pH regulates NOX-independent NET formation, and modifying pH may help to regulate NET formation during sterile inflammation or potential damage caused by compounds such as ionomycin, secreted by Streptomyces, a group of Gram-positive bacteria well known for producing antibiotics.